Normal-state properties of the quasi-one-dimensional superconductor Ta4Pd3Te16. (24th May 2019) - Jiao, Wen-He; Huang, Yi-Na; Xu, Xiao-Feng; Li, Yu-Ke; Liu, Yi; Wang, Zhi-Cheng; Xu, Xing-Liang; Feng, Yuan-Xin; Feng, Chun-Mu; Cao, Guang-Han
Abstract: We examined the physical properties of the quasi-one-dimensional superconductor Ta4 Pd3 Te16 in the normal state by detailed measurements of susceptibility, in-plane anisotropic resistivity, magnetoresistance, Hall resistivity, and Seebeck coefficient. The large Wilson ratio, as inferred from normal-state susceptibility, indicates strong electron–electron interaction. The Hall and Seebeck coefficients show not only significant temperature-dependent behavior, indicating the multiband effect, but also an obvious anomaly around T 1 = 40 K. Analyses of both the Hall resistivity and thermopower using a two-band model indicate that the electrons dominate the electrical transport at low temperatures. Our results imply that it is the quantum fluctuations of the charge order taking place in the temperature range 30–50 K that may result in the abnormal normal-state properties of Ta4 Pd3 Te16 .